Stasis and Change in Public School District Racial/Ethnic Segregation, 1993-2015 - Meredith P. Richards; Kori James Stroub; Camila Cigarroa Kennedy (SAGE Publishing, 2020)
Scholars have often suggested that racial integration is inherently unstable-a transition point in the racial transformation of neighborhoods and schools. While much empirical attention has been paid to documenting changes in segregation in public school districts, in this study we provide initial evidence focusing on the stability of segregation patterns. We calculate annual measures of district racial/ethnic segregation from the National Center for Education Statistics Common Core of Data from 1993 to 2015. Our findings suggest that despite relatively high and stable levels of segregation nationally, stability is the rule, rather than the exception, for the majority of public school districts. Using a taxonomy of severity and stability derived from previous scholarship, we find that most districts are "stably integrated," with a minority "stably segregated" or exhibiting meaningful change. Our findings suggest that further attention to the characteristics and practices of "stably integrated" districts may be warranted.